Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1536/ihj.20-824
|View full text |Cite
|
Sign up to set email alerts
|

Time Course and Risk Factors of New-Onset Complete Atrioventricular Block After Transcatheter Aortic Valve Implantation

Abstract: In this study, we aimed to investigate the time course of new-onset complete atrioventricular block (CAVB) and its reversibility after transcatheter aortic valve implantation (TAVI). We analyzed 206 consecutive patients without baseline CAVB who underwent successful TAVI. The incidence of new-onset CAVB was determined to be 12.6% (26/206). Among these patients, 14 recovered from CAVB within 2 weeks (6.8%, 14/206), while the remaining 12 (5.8%, 12/206) underwent permanent pacemaker (PPM) insertion. Among the 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Although a higher risk of advanced conduction abnormalities, including new-onset left bundle branch block and high-grade atrio-ventricular block requiring pacemaker assistance, after TAVR than after SAVR has been well demonstrated in previous studies [ 23 , 24 ], the PPM insertion rate of 14.3% in the TAVR group was relatively high considering recent studies reporting PPM insertion rates of 4.0% to 12.7% [ 25 , 26 ]. In addition, a previous study at our institution reported that 5.8% of 206 patients underwent PPM insertion after a TAVR procedure [ 27 ]. This might be attributed to the fact that patients with CKD have a high burden of calcium in the cardiovascular system including a diseased aortic valve [ 28 ], which is vulnerable to conduction block after the TAVR procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Although a higher risk of advanced conduction abnormalities, including new-onset left bundle branch block and high-grade atrio-ventricular block requiring pacemaker assistance, after TAVR than after SAVR has been well demonstrated in previous studies [ 23 , 24 ], the PPM insertion rate of 14.3% in the TAVR group was relatively high considering recent studies reporting PPM insertion rates of 4.0% to 12.7% [ 25 , 26 ]. In addition, a previous study at our institution reported that 5.8% of 206 patients underwent PPM insertion after a TAVR procedure [ 27 ]. This might be attributed to the fact that patients with CKD have a high burden of calcium in the cardiovascular system including a diseased aortic valve [ 28 ], which is vulnerable to conduction block after the TAVR procedure.…”
Section: Discussionmentioning
confidence: 99%